PENGEMBANGAN APLIKASI PENCARIAN DOKUMEN AKREDITASI BERBASIS WEB PADA UNIVERSITAS MUHAMMADIYAH JAMBI - Muhammad Ikhsan; Oka Ediansa; Helmina Helmina; Zulfikri Akbar; M. Jumain (FORTECH (Journal of Information Technology), 2026)
Accreditation document management in higher education requires organized storage, consistent classification, and fast retrieval of supporting evidence. In practice, accreditation documents are often distributed across study programs, faculties, quality assurance units, and various storage folders, making retrieval time-consuming and increasing the risk of incomplete evidence during accreditation preparation. This study aims to develop a web-based accreditation document search application at Universitas Muhammadiyah Jambi using the Prototype method. The development stages include requirements gathering, quick design, prototype construction, user evaluation, refinement, implementation, and functional testing. The system was built using PHP, MySQL, HTML, CSS, Bootstrap, and JavaScript. The main features include user login, document dashboard, document upload, keyword-based search, filtering by faculty, study program, accreditation criteria, document type, and year, document management, preview, download, and recap by criteria. Functional testing using ten black-box scenarios showed that core features operated according to the expected results. The system contributes by providing a centralized accreditation document repository that supports faster document retrieval, more orderly evidence classification, and internal quality assurance activities. Further studies should measure retrieval time, user satisfaction, and system usability quantitatively.